Sooz - Delgado, O.S. (Escuela de Lenguas Modernas, Universidad de Costa Rica, 2010)
My existence ought to be described in terms of a cage imprisoning my spirit. My mother, Molly, was the stout bars that parted me from the world, and my sister, Lilly, was the aethereal spaces between these bars that grant me vision upon life outside confinement. Lilly was my precious little window, and there would never have been life in me without her. We have spent our lives ridiculously close to each other since the moment of our conception. It may sound silly, but I think I fell in love with her the very first time I opened my eyes inside Molly?s womb. These two women have shaped my years. Everything I am is their manufacture.